CAPTAIN AMERICA : ALLIES & ENEMIES - Williams, Rob; Isaacs, Rebekah; Dahlhouse, Andrew; Brennan, Tom (New York, N.Y. : Marvel Worldwide, 2011)
Tegneserie. Collects the super-soldier Captain America's various adventures with other members of the Avengers supergroup, including the Falcon, Agent Thirteen, and the Black Widow
Indhold: Captain America and the Falcon / writer, Rob Williams ; artist, Rebekah Isaacs. Captain America and the first Thirteen / writer, Kathryn Immonen ; artist, Ramon Perez. Captain America and Crossbones / writer, William Harms ; artist, Declan Shalvey. Captain America and the Secret Avengers / writer, Kelly Sue Deconnick ; artist, Greg Tocchini. Captain America and Batroc / writer, Kieron Gillen ; artist, Renato Arlem
Keywords: America, Captain (Fictitious character) -- Comic books, strips, etc; Graphic novel